2007
DOI: 10.1021/la703322d
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Verification of an Exact Evanescent Light Scattering Model for TIRM

Abstract: Total internal reflection microscopy (TIRM) is a method for the precise measurement of interaction potentials between a spherical colloidal particle and a wall. The method is based on single-particle evanescent wave light scattering. The well-established model used to interpret TIRM data is based on an exponential relation between scattering intensity and particle wall distance. However, applying this model for a certain range of experimental parameters leads to significant distortions of the measured potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 15 publications
2
30
0
Order By: Relevance
“…40,41 We find that scattering intensity fits an exponential decay fairly well above h > 50 nm with λ = 145 ± 5 nm up to about h ≈ 500 nm, where the signal is too weak to resolve height information.…”
Section: ■ Introductionmentioning
confidence: 92%
“…40,41 We find that scattering intensity fits an exponential decay fairly well above h > 50 nm with λ = 145 ± 5 nm up to about h ≈ 500 nm, where the signal is too weak to resolve height information.…”
Section: ■ Introductionmentioning
confidence: 92%
“…Intensity ratios that are higher than expected from the maximum bond height displacement, might be explained by a deviation from the idealized exponential decay model. Recently, it has been shown that multiple reflections between a particle and the surface can cause a distortion of the exponential model, especially for large penetration depths (close to half the excitation wavelength) and small particle heights (Helden et al 2006, Hertlein et al 2008. For a small penetration depth of 132 nm, which is on the order of the 95 nm penetration depth in our system, simulations with 1.6 µm diameter polystyrene particles pointed to a reduction in scattered light intensity near the surface of approximately 15%, leading to a reduced measured height change.…”
Section: Intensity Fluctuations Of Bound Particlesmentioning
confidence: 99%
“…Also, Borghese et al [49] studied the radiation torque and force on optically linear nanostructures using an angular spectrum representation of a focused laser beam after passing through a high-NA objective lens, with details of the procedure used available from Borghese et al [50] dealing with optical trapping of nonspherical particles in the T-matrix formalism. In 2008, Hertlein et al [51] used a PWS in association with the discrete sources method (DSM) -which may be viewed as a variant of EBCM -to study an evanescent light scattering model for total internal reflection microscopy (TIRM), including an experimental verification. In 2001, a PWS representation consisting of about a hundred components was used by Nieminen et al [52] for the calculation, associated with optical measurements of laser trapping forces on a non-spherical particle.…”
Section: Use Of Plane Wave Spectra For Arbitrary Shaped Beamsmentioning
confidence: 99%